2021
DOI: 10.1186/s13102-021-00260-w
|View full text |Cite
|
Sign up to set email alerts
|

What are the impact and the optimal design of a physical prehabilitation program in patients with esophagogastric cancer awaiting surgery? A systematic review

Abstract: Background Substantial postoperative complications occur after tumor resection for esophagogastric cancers. Physical prehabilitation programs aim to prepare patients for surgery by improving their functional status with the aim of reducing postoperative complications. This systematic review aims to summarize the effects of physical prehabilitation programs on exercise capacity, muscle strength, respiratory muscle function, postoperative outcomes, and health-related quality of life and to determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…The literature research revealed 24 out of 55 studies with Oxford evidence levels of 1 and 2 focusing on prehabilitation prior to intra-abdominal or thoracic surgery predominantly in the oncologic area and including 353,014 patients for analysis ( 27 , 29 32 , 34 , 36 39 , 43 , 48 , 49 , 51 , 52 , 55 , 56 , 58 , 60 , 65 , 68 , 69 , 72 ). One guideline was related to the general population with recommendations for physical activity ( 22 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The literature research revealed 24 out of 55 studies with Oxford evidence levels of 1 and 2 focusing on prehabilitation prior to intra-abdominal or thoracic surgery predominantly in the oncologic area and including 353,014 patients for analysis ( 27 , 29 32 , 34 , 36 39 , 43 , 48 , 49 , 51 , 52 , 55 , 56 , 58 , 60 , 65 , 68 , 69 , 72 ). One guideline was related to the general population with recommendations for physical activity ( 22 ).…”
Section: Resultsmentioning
confidence: 99%
“…A total of 18 (78%) studies investigated different types of exercise interventions and exercise testing. Thirteen studies applied inspiratory muscle training (IMT) to prepare patients for surgery ( 30 , 32 , 36 , 43 , 48 , 49 , 52 , 55 , 58 , 60 , 68 , 69 , 72 ). Five studies reported high intense interval training (HIIT) as modality ( 27 , 29 , 34 , 60 , 68 ), and in five studies, the intensity was controlled with various target measurements of intensity ( 27 , 29 , 55 , 56 , 72 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Qualitative and quantitative skeletal muscle assessment demonstrated independent associations with fitness and clinical outcomes among cancer survivors (50,51). For example, physical prehabilitation programs could prepare patients for surgery by improving their functional status with the aim of reducing postoperative complications (52,53). The number of cancer survivors with less complications is continuously increasing due to improved screening, diagnoses, imaging, endoscopic-, histopathologic and molecular examination methods, and interdisciplinary defined treatments using advanced technology in local therapeutic modalities and effective novel approaches such as molecular targeted systemic therapy and immunotherapy and their combination.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it is also anticipated to bring about changes in the lifestyle behavior of the older patients postsurgery, facilitating their return to premorbid function and maintaining a healthy lifestyle 41. It has been shown that preoperative physical programs are feasible and safe and may be beneficial for improving exercise capacity, muscle strength, respiratory muscle function, health-related quality of life, postoperative complications, and length of stay in the surgical older population 42. A combination of resistance, aerobic, balance, and flexibility exercises is encouraged to provide comprehensive training for the older adults.…”
Section: Exercisementioning
confidence: 99%